The quantum‐confined Stark effect and localization of charge carriers in AlxGa1‐xN/AlyGa1‐yN quantum wells with different morphologies. Issue 3 (7th February 2013) - Shevchenko, E. A.; Jmerik, V. N.; Mizerov, A. M.; Nechaev, D. V.; Sitnikova, A. A.; Ivanov, S. V.; Toropov, A. A.; Toropov, Alexey; Ivanov, Sergey
Abstract We present a comparative study of three samples with a single Al0.3Ga0.7N/Al0.4Ga0.6N quantum well (QW) grown by plasma‐assisted molecular beam epitaxy on c ‐sapphire substrates with an AlN buffer deposited under different Al/N flux ratios. We show by means of transmission electron microscopy that strong N‐rich growth conditions result in a three‐dimensional morphology that is inherited by the QW. As a result, the QW is corrugated on the size scale of the QW photoluminescence (PL) wavelength (∼300 nm). The Al‐rich conditions lead to a two‐dimensional growth and formation of a plane QW with flat interfaces. The PL line in the corrugated QW is 5 times more intensive and shifted toward larger energies by ∼200 meV, as compared with the plane QW. The superior emission properties are explained by simultaneous action of several factors such as suppression of the quantum‐confined Stark effect, enhanced carrier localization, and improved efficiency of light extraction. (© 2013 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)